A SEMIOTIC ANALYSIS ON ICON, INDEX, AND SYMBOL IN GET OUT MOVIE - Norman Baharsyah; Ardayati Ardayati; Agus Triyogo (JELLT (Journal of English Language and Language Teaching), 2020)
The problem of this study was â€What are the icons, indexes, and symbols in Get OutÂ  movie?â€. There were primary sources and secondary sources in this study. The primary source used in this study was Get Out movie while the secondary sources were several books, journals, and articles to support this study. The objective of this study was to describe the icons, indexes, and symbols in Get Out Movie by using Charles Peirce's theory. This study used descriptive qualitative research. In collecting the data, the writer used library research, in which the writer went to find desirable references consisted of books, journals, and articles. In analyzing the data, the writer identified and classified the data first, then the writer did some reduction to the data. The writer only chose relevant data in several key scenes in the movie which were contributive to the plot and removed the redundant and unnecessary ones. After conducting the study, the writer found out that there were thirty signs in Get Out movie. The result showed that the thirty signs found in the movie were classified into three icons, twenty indexes, and seven symbols.